COLLABORATIVE GOVERNANCE DALAM PEMBANGUNAN SEKTOR PERTANIAN DI KABUPATEN BANDUNG - Iyoega, Rofi' Ramadhona (Universitas Medan Area, 2020)
The agricultural sector is important in national economic development, especially as a provider of employment and as the main source of income for rural communities. Development in the agricultural sector requires the support of all stakeholders, the government's limited role in accommodating the needs in this sector then gave birth to a concept of a collaboration called Collaborative Governance. This research was conducted in Bandung Regency, aimed at finding out the implementation of Collaborative Governance, knowing the reach of farmers to the market, knowing the marketing media used and the problems faced by farmers in accessing the market. Data in this study were collected through interviews, then analyzed using qualitative data analysis techniques. The results showed the role of local government was very dominant and vice versa universities contributed very minimally. The reach of farmers to the market is still very low, only a small proportion of farmers have marketed their products outside the region. In marketing their agricultural products, farmers have started to utilize online media. The government is expected to assist farmers in opening market access through the use of marketing technology or by bringing farmers together with investors.